Effect Of Mindfulness Based Cognitive Therapy (MBCT) on Anxiety and Blood Pressure for Hypertension: A scoping review - Irawan am, Ady; Janmabhumi, Anjani; Wulandari, Ziara Arum; Putri, Anggie Pradana; Santoso, Aris Prio Agus (Institut Citra Internasional, 2024)
Hypertension, a prevalent and chronic medical condition, is often associated with elevated anxiety levels, contributing to its progression and complications. Mindfulness-Based Cognitive Therapy (MBCT) has emerged as a potential intervention to address both anxiety and hypertension. This scoping review aims to explore the existing literature on the effect of MBCT on anxiety and blood pressure in individuals with hypertension. Methods: A comprehensive search was conducted across electronic database, including Garuda, PubMed, Web of Science (WOS), and Science, for relevant articles published between 2013 to 2023. The searching process utilized PCC approach (Population: adult with hypertension; concept (C): mindfulness based cognitive therapy (MBCT), anxiety, high blood pressure, hypertension, cardiovascular disease; context (C): clinical and community settings). Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) was employed as guideline to the screening process of articles in this study. A total of eight articles were evaluated their quality using The Joanna Briggs Institute Checklist. Some characteristics of mindfulness were identified: MBCT general, MBCT for perinatal depression (MBCT-PD), MBCT for anxiety (MBCT-A), and telephone delivered MBCT (MBCT-T). In general, the timeframe for conducting MBCT is eight weeks, with each session lasting 2 to 2.5 hours. MBCT demonstrates promise as an adjunctive intervention for managing anxiety and blood pressure in individuals with hypertension. While preliminary evidence suggests its potential benefits, further research is needed to establish its efficacy and refine its application in clinical practice. Integrating MBCT into comprehensive hypertension management strategies may offer a multifaceted approach to improving the well-being of individuals with hypertension.